2011
DOI: 10.1063/1.3642956
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural comparison of silicon solar cells’ front-side Ag contact and the evolution of current conduction mechanisms

Abstract: Microstructures of front-side Ag contact of crystalline Si solar cells fired at temperatures from below to above optimal were systematically investigated using advanced electron microscopy. Ag pastes studied included commercial pastes and an experimental paste containing nano-sized metallic Zn additive. Microstructures of optimally fired cells determined from cross-sectional and top-view images were found to be consistent with a primary tunneling mechanism for current flow (a “nano-Ag colloids assisted tunneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 15 publications
3
56
0
Order By: Relevance
“…For example Li et al showed an improvement in cell characteristics with the addition of nano -ZnO to the glass containing silver powder [5] . Another possibility is vary the oxygen activity of the glass forming melt.…”
Section: Introductionmentioning
confidence: 99%
“…For example Li et al showed an improvement in cell characteristics with the addition of nano -ZnO to the glass containing silver powder [5] . Another possibility is vary the oxygen activity of the glass forming melt.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines are developed for the case when current conduction through Ag crystallites is prevalent at the Ag/n þ Si interface. In some previous studies, Ag screen-printed contact formation to n þ Si was observed presumably entirely through nano-Ag colloids dispersed in the interfacial glass layer (as no Ag crystallites were observed at the contact interface) [5,6]. For such cases our guidelines are not applicable.…”
Section: Guidelines To Tailor Pyramid Height Distributionsmentioning
confidence: 90%
“…Tunnelling through the interfacial glass may be enhanced by dispersed Ag in the glass layer [3,4]. Some authors have recently stressed the importance of nano-Ag colloids dispersed in the interfacial glass layer for contact formation and suggested that Ag crystallites may not be necessary for contact formation [5,6]. The nano-Ag colloids dispersed in glass are assumed to aid a multi-step tunnel contact through the glass layer.…”
Section: Introductionmentioning
confidence: 98%
“…29,30 The geometry, morphology, and components of the conductive lines have been studied to minimize shading of the cells while maintaining good conductance. [31][32][33] Research on the conductive lines has typically focused on the conductor line microstructure throughout the firing process 34 and the interface between the screen-printed conductive lines and the emitter as a function of precursor constituents to optimize the initial electrical performance. 30,[34][35][36][37][38] The microscopic mechanisms that result in the formation of the low resistance contact between the silver conductive lines and the solar cell are still being uncovered, 28 but two prevailing models are generally accepted.…”
Section: Mesoscale Description Of Solar Cell Interfaces and Contactsmentioning
confidence: 99%
“…[31][32][33] Research on the conductive lines has typically focused on the conductor line microstructure throughout the firing process 34 and the interface between the screen-printed conductive lines and the emitter as a function of precursor constituents to optimize the initial electrical performance. 30,[34][35][36][37][38] The microscopic mechanisms that result in the formation of the low resistance contact between the silver conductive lines and the solar cell are still being uncovered, 28 but two prevailing models are generally accepted. One hypothesis suggests that the Ag becomes dissolved within the molten glass frit, and upon cooling down, the supersaturated solution allows large grain growth at the Si interface causing a Schottky-barrierlike boundary that acts more Ohmic as the emitter doping concentration is increased to n þþ levels.…”
Section: Mesoscale Description Of Solar Cell Interfaces and Contactsmentioning
confidence: 99%